The Role of microRNA in the Regulation of BST-2 (bone marrow stromal antigen-2) Gene Expresion - Robi Akollo; Vernando Yanry Lameky Lameky; Sahrir Sillehu (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2026)
Background: MicroRNA (miRNA) is a non-coding RNA molecule that plays an important role in the regulation of post-transcriptional gene expression and is involved in various biological processes, including immune responses and disease development. MicroRNAs are involved in the regulation of various genes, one of which is Bone Marrow Stromal Antigen 2 (BST-2). Purpose: This study aims to examine the role of microRNA in regulating BST-2 gene expression. Methods: This study used a scoping review approach to examine the role of microRNA in the regulation of BST-2 gene expression. Research articles were obtained from the PubMed, Scopus, and Google Scholar databases, with publication years ranging from 2015 to 2025, and were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: The results of the review show that several microRNAs, namely miR-129-5p, miR-760, miR-155, and miR-451a, act as negative regulators of BST-2 gene expression. MicroRNAs can bind to BST-2 mRNA, inhibiting translation and thereby reducing the production of BST-2 protein. The role of microRNA in regulating BST-2 has been identified in clinical various conditions, particularly cancer. Conclusions: microRNAs play a role in the regulation of BST-2 gene expression and have the potential to be developed as therapeutic targets or biomarkers in diseases associated with BST-2 dysregulation.